Legitimação institucional do jornalismo informativo nas mídias sociais digitais: estratégias emergentes no conteúdo de Zero Hora no Twitter - Carvalho, Luciana Menezes (2010)
This thesis has as context the institutional legitimation crisis that occurs in our society and affects the mediating role of journalism informative, maximized by the interactive practices of digital social media, with their abilities for participation, sharing and decentralized distribution of messages by public. This logic is opposed to the broadcast model of mass media that mark the process of journalism legitimacy. The research problem asks: what strategies of institutional legitimacy emerge in the contents of messages postedby the newspaper Zero Hora on Twitter? The overall goal is to understand the strategies used by journalism in order to gain institutional legitimacy through the use of digital social media. The specific objectives are: to recognize the institutional uses of Twitter for Zero Hora, identifying the emerging strategies of institutional legitimacy for the posts of Zero Hora on Twitter, watch as Zero Hora develops its mediation role in the informational use of Twitter as social media, analyze the relationship between the mediating role of journalism and the characteristics of digital social media disintermediation. The Hybrid methodology is qualitative, using content analysis (CA), semi-structured interviews and participant observation in the writing of Zero Hora. The Content Analysis (CA) was performed in two corpora relating to news coverage carried out by Zero Hora with a one year interval between them. The results of the CA was crossed with data from participant observation and interviews, relating to the theoretical analysis. The main uses of Twitter found relate to the categories of information dissemination, participation, sharing and conversation, making to emerge strategies of institutional legitimacy by journalism. The analysis indicates for continuities and ruptures in the process of legitimation by journalism on the passage of the emission centered logic of mass media for decentralized and interactive logic by digital social media. Comparing the two corpora analysis was possible to observe a transformation in the mediating role of the news organization's Twitter, with a growing ownership of the possibilities of digital social media participation, in which the public is increasingly included.